Analisis Peran Elemen Marketing Mix Jasa Terhadap Keputusan Menggunakan Jasa Perbankan pada BSI Wilayah Pekalongan - Emira Imania Utami; Amron Amron; Dwi Eko Waluyo; Pradana Jati Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research examines the influence of the process, people, and physical evidence elements on consumers' purchasing decisions at Bank Syariah Indonesia in the City and Regency of Pekalongan. A quantitative approach was applied using data collected from 108 respondents, which were analyzed using SmartPLS through the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results reveal that all three service marketing mix components exert a positive and significant impact on purchasing decisions. Notably, the process element emerges as the most dominant factor in shaping customers' buying choices. These results highlight the importance of optimizing service processes to enhance customer decision-making. This study contributes theoretically to the marketing management literature regarding consumer behavior in the Islamic banking industry, as well as practically to Bank Syariah Indonesia in developing marketing strategies and optimizing digital-based services.